Compliance to Drug Therapy in Inflammatory Bowel Diseases: A Monocentric Experience - aouroud, hala; Errami, Adil Ait; Essaidi, Nayala Hanane; Lairani, FZ.; Nacir, O.; Oubaha, Sofia; Samlani, Zouhour; Krati, khadija (International Journal of Innovative Research in Medical Science, 2023)
Poor therapeutic compliance in inflammatory bowel diseases (IBD) has a negative impact on treatment efficacy and patients' quality of life. Addressing this issue requires an understanding of the factors involved, which include patient-related factors, socioeconomic conditions, treatment, and healthcare system factors. The aim of this study was to identify the factors responsible for poor therapeutic compliance in patients with IBD in our context. We conducted a prospective study involving 120 patients with IBD over a 10-month period. Data was collected using two questionnaires: one general questionnaire exploring factors influencing compliance and another specific one (Morisky Score) assessing the level of compliance. Of the 120 patients included, the average age was 39.66 years, with a female predominance. Crohn's disease was the most common pathology (71.7%), and 75% of patients were adherent to treatment. Lack of means was the most common reason for treatment abandonment. Bivariate analysis revealed a significant correlation between compliance, gender, monthly income, number of hospitalizations, number of daily doses, cost, perception of treatment importance, access to the treating physician, and mode of communication. Therefore, improving therapeutic compliance requires continuous support from healthcare professionals and the healthcare system, as well as responsible patients.